Bridging the Skills Gap: A Readiness Assessment of Tanzania Revenue Authority Personnel for Artificial Intelligence-Driven Customs Risk Management - Ndahani Ng`wasa (Universitas Negeri Makassar, 2025)
The integration of artificial intelligence (AI) into customs risk management has become a strategic priority for revenue authorities worldwide seeking to enhance trade facilitation, improve revenue collection, and combat illicit trade. The Tanzania Revenue Authority (TRA) has made substantial investments in digital transformation, including the deployment of AI-powered Electronic Tax Stamp systems, drone surveillance technology, and the Tanzania Customs Integrated System (TANCIS). However, the successful adoption of these technologies depends critically on the readiness of the workforce that must operate, manage, and maintain them. This study assesses the readiness of TRA personnel for AI-driven customs risk management, focusing on current skills, knowledge gaps, training needs, and organizational preparedness. Using a mixed-methods approach involving surveys (n = 178) and semi-structured interviews (n = 22) with TRA customs officers across four regions of Tanzania, the study identifies significant skills gaps in data literacy, AI system operation, risk analytics, and ethical AI use. The findings reveal that while 78% of respondents expressed positive attitudes toward AI adoption, only 23% reported having received any formal training in AI or data analytics. Key barriers to readiness include inadequate training infrastructure, resistance to disruptive innovation, limited cross-functional collaboration, and financial constraints. The study proposes a capacity-building framework tailored to TRA's operational context, addressing both technical competencies and organizational culture.